A rhetoric of reflection - Yancey, Kathleen Blake, 1950- (Utah State University Press, 2016)
"This research and practice is taking up new questions, in new sites of activity, with new theories. It includes attention to transfer of writing knowledge and practice to teaching and assessment; to portfolios; to linguistic and cultural difference; and to various media, including print and the digital"--Provided by publisher